FACTORS ASSOCIATED WITH UNINTENDED PREGNANCIES AMONG WOMEN OF CHILDBEARING AGE IN EAST JAVA PROVINCE, INDONESIA - Kusumaningtyas, Chofifah Ayu; Darmawan, Wildan Satrio; Fareza, Artamalia Rizky; Qotrunnada, Miranda Zannuba; Sukarno, Sukarno; Prapatpong, Pornpan; Saputro, Sigit Ari (Jurnal Biometrika dan Kependudukan, 2025)
Unintended pregnancies are still a major global reproductive health issue since affecting the risk of maternal and child health. This study aims to determine the prevalence of unintended pregnancies and its associated factors among women of childbearing age in East Java. We explored secondary data analysis from the most recent 2019 Program Performance and Accountability Survey. Frequency distribution tables and cross-tabulations were used to describe the participants characteristics. The univariable and multivariable logistic regression analysis was utilized to find the effect size of predictors on unintended pregnancies with 95% Confidence Intervals (CIs). All analysis were done using STATA version 17 with complex survey data design. This study revealed that the weighted prevalence of unintended pregnancies was 14.95% (95% CI: 13.47 – 16.42) among current married women. The main reasons of unintended pregnancies were living in urban areas (aOR: 1.36; 95% CI: 1.05–1.77), from rich household wealth index (aOR: 1.82; 95% CI: 1.17–2.83), and used electronic media (aOR: 1.83; 95% CI: 1.21–2.75). Policies to reduce unintended pregnancies should prioritize married women in urban areas, particularly those who have good access to electronic media, and come from more prosperous households. The provision of accurate and standardized contraceptive information through digital-based family planning education, facilitated by qualified health communicators, plays a pivotal role in mitigating misinformation. BKKBN needs to encourage the optimization of the Kampung KB and Bangga Kencana programs to increase access to effective contraceptive methods, notably LARCs.